Histopathological and histochemical study of mastitis in sheep - Asseel M. Rahawi; Hadil B. Al-Sabaawy; Hana Ismail (Iraqi Journal of Veterinary Sciences, 2022)
Ovine mastitis is considered one of the problems that cause economic losses through its impact on milk production, which is unfit for human consumption. The current study aimed to shed light on mastitis in sheep in different areas of Mosul city. The results of the recent study showed the presence of mammary macroscopic and microscopic changes. Macroscopic changes were represented by the large size of the udder and changes in the color and texture, as well as clarity of sloughing and desquamation of the skin with clear exudation, especially in advanced cases. On the other hand, other samples showed the presence of hard nodules on the udders. In contrast, the histological changes represented by degenerative and necrotic changes 3.5%, and 21.4% of the sample appeared to suffer from liquefactive necrosis and abscesses infiltrated with inflammatory cells, 25% of the samples infected with granulomatous mastitis (nodular mastitis), other models showed that the udder infected with atrophy and metaplasia in the rate of 21%, thickening of the blood vessel wall with clot represented 14.2% and the deposition of calcium salt was 14.2%. The current study concludes that mastitis in sheep is widespread in sheep raised in different areas of Mosul city.